Jordan : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2004)
This Selected Issues paper and Statistical Appendix on Jordan underlies stabilization and structural transformation of the economy. Current fiscal policy appears to be broadly sustainable and should be sufficient to allow for the continued fall in the debt burden, absent large external macroeconomic shocks. Over the past decade, Jordan has made commendable progress in replacing an informal family-based social safety system with well-defined and well-targeted social protection institutions. The government will need to remain committed to periodic increases of fuel prices to close the gap between domestic and international petroleum product prices.